2014
DOI: 10.3390/v6020489
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analyses of Avocado sunblotch viroid Reveal Differences in the Folding of Plus and Minus RNA Strands

Abstract: Viroids are small pathogenic circular single-stranded RNAs, present in two complementary sequences, named plus and minus, in infected plant cells. A high degree of complementarities between different regions of the RNAs allows them to adopt complex structures. Since viroids are naked non-coding RNAs, interactions with host factors appear to be closely related to their structural and catalytic characteristics. Avocado sunblotch viroid (ASBVd), a member of the family Avsunviroidae, replicates via a symmetric RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
3
18
1
Order By: Relevance
“…2b). As indicated above, such an observation is consistent with others made previously in gels of similar porosity, but using ml ASBVd (+) and (À) RNAs [23], and with the more stable conformation predicted for the mc ASBVd (+) RNA by the three software programs (see above). However, we found that while the ml ASBVd (À) RNA resulting from self-cleavage migrated in 8 % gels as a sharp band, the ml ASBVd (+) RNA also from selfcleavage migrated as a blurred band (data not shown), thus hinting at the co-existence of different conformations in the latter.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…2b). As indicated above, such an observation is consistent with others made previously in gels of similar porosity, but using ml ASBVd (+) and (À) RNAs [23], and with the more stable conformation predicted for the mc ASBVd (+) RNA by the three software programs (see above). However, we found that while the ml ASBVd (À) RNA resulting from self-cleavage migrated in 8 % gels as a sharp band, the ml ASBVd (+) RNA also from selfcleavage migrated as a blurred band (data not shown), thus hinting at the co-existence of different conformations in the latter.…”
Section: Resultssupporting
confidence: 91%
“…In vitro SHAPE of mc ASBVd (+) and (À) RNAs generated well-resolved structures that were almost identical with the two acylating reagents used (NMIA and NAI), in line with the adoption of predominant conformations by both RNAs in vitro as inferred from their migration as single bands in non-denaturing PAGE. These structures also agree with: (i) those predicted in silico, particularly with the RNAfold software program, and (ii) those derived previously from in vitro SHAPE [24], while differing somewhat from others obtained with the same in vitro approach [23]. Furthermore, the rod-like conformations proposed in vitro for the mc ASBVd (+) and (À) RNAs are also consistent with the solubility in 2 M LiCl of the mc ASBVd RNAs extracted from infected tissue, mainly formed by the (+) strand [45], and of the ml ELVd (+) and (À) RNAs resulting from in vitro self-cleavage that adopt quasi-rod-like secondary structures [36].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations